2007
DOI: 10.2174/138161207780487593
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Innate Immune System in Atherosclerotic Disease

Abstract: Innate immunity is the first line of defence against invading micro-organisms. The family of Toll-like receptors (TLRs) recognizes pathogen-associated molecular patterns (PAMPs) that are carried by the invading micro-organisms. Infectious pathogens have been implicated to play an important role in atherosclerosis. Nowadays, evidence is accumulating that TLRs play an important role in the initiation and progression of atherosclerosis too. A lot is known about the exogenous ligands that are able to activate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 118 publications
(137 reference statements)
0
31
0
Order By: Relevance
“…Previous epidemiological studies have proved that exogenous bacterial ligands can induce an inflammatory response in the arterial wall and initiate atherosclerosis [8] , and therefore, a link between atherosclerosis and TLRs has been established. Experimental data have shown that lipopolysaccharide (LPS) and peptidoglycan (PGN), both potent TLR activators, can accelerate plaque formation in atherosclerotic mice [6] . These results point to a potential role of TLR-2 and TLR-4 in the pathogenesis of atherosclerotic disease.…”
Section: The Role Of Tlrs In Cvdmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous epidemiological studies have proved that exogenous bacterial ligands can induce an inflammatory response in the arterial wall and initiate atherosclerosis [8] , and therefore, a link between atherosclerosis and TLRs has been established. Experimental data have shown that lipopolysaccharide (LPS) and peptidoglycan (PGN), both potent TLR activators, can accelerate plaque formation in atherosclerotic mice [6] . These results point to a potential role of TLR-2 and TLR-4 in the pathogenesis of atherosclerotic disease.…”
Section: The Role Of Tlrs In Cvdmentioning
confidence: 99%
“…Fundamental cells of the innate immune system, namely monocytes and macrophages, are present within atherosclerotic lesions and express various pattern-recognition receptors, among which, Toll-like receptors (TLRs). TLRs occur in atherosclerotic lesions [5] where they are triggered by both exogenous (bacterial and viral pathogens) and endogenous (tissue damage-associated) molecules [6] . Several endogenous ligands for TLRs are expressed during inflammation in atherosclerotic plaques or ischemic heart where they might play a role in disease pathogenesis and progression.…”
Section: Introductionmentioning
confidence: 99%
“…The American Heart Association suggested that the blood C-reactive protein (CRP) level is a risk factor in coronary disease development [9]. In addition, the immune capacity in the human body plays a critical role in the induction and deterioration of atherosclerosis, with monocytes/macrophages playing critical roles in this action [10]. Monocyte participation in the progression of atherosclerotic plaques was demonstrated in the 1970s, with monocyte aggregation manifested in atherosclerotic lesions [11].…”
Section: Introductionmentioning
confidence: 99%
“…The innate immune system plays a major role in the initiation and propagation of atherosclerosis, with monocytes/macrophages being the key players in this process (Oude Nijhuis et al, 2007).…”
Section: Inflammation In the Atherosclerotic Heart Diseasementioning
confidence: 99%